Feeding strategies and ageing time alter calpain system proteins activities and meat quality of Braford steers - Coria, María Sumampa; Pighin, Darío Gabriel; Grigioni, Gabriela Maria; Palma, Gustavo Adolfo (Asian-Australasian Association of Animal Production Societies, 2022)
Objective: The aim of this study was to evaluate the effect of ageing and feeding strategies on the calpain protease system and meat quality traits in Braford steers. Methods: Thirty Braford steers were employed; 15 animals were supplemented with corn silage during finishing and 15 were kept only on pasture. Meat quality traits and calpain system protein activity were evaluated in longissimus thoracis et lumborum (LTL) steaks aged for 2, 7, 14, and 21 days. Results: Aged meat showed higher pH and calcium content, while Warner Bratzler shear force (WBSF) decreased to day 21. No interaction between ageing and diet was seen for quality traits. Steers finished with corn silage showed higher values of water holding capacity, WBSF and free calcium, and lower values of pH and cooking loss. Calpain and calpastatin activities decreased with ageing. Finishing steers on pasture produced higher values of calpains and lower values of calpastatin activities. The higher values of calpain 1 activity were observed in muscles aged 2 days from pasture finished animals, and the lower activity of the inhibitor in the 21 days aged samples of the same group. Conclusion: These results suggest a diet by ageing interaction in calpains and calpastatin and this interaction impact in Warner Bratzler Shear Force in Braford LTL muscle.